Measuring peak angular velocity of knee extension during unloaded kicking: a pilot study - A. Malik Zulezwan, - Jos Vanrenterghem, Burniston Jatin G., (Universiti Pendidikan Sultan Idris, 2016)
Measuring peak angular velocity of knee extension during unloaded kicking: a pilot study by A. Malik Zulezwan, - Jos Vanrenterghem, Burniston Jatin G.,